How the Exponential Function is Taught: A Praxeological Analysis of Indonesian Textbooks - Dharma Suarka, Ni Komang Savitri; Frarisia, Tata; Rahma, fauziah annisa (Universitas Islam Sultan Agung, 2025)
Multiplying repeated numbers yields an expression for exponent numbers. Numerous studies have shown that students still experience difficulties when learning exponents. A particular approach to assist students in overcoming their challenges is to use textbooks as a study resource. This study aims to evaluate the material provided in the Indonesian mathematics textbook about the exponent and exponential function subjects. This study employed a qualitative research design utilising a content analysis approach, using a mathematics textbook for observation and documentation. There were two primary stages to the analytical process: the logos bloc analysis and the praxis bloc analysis. The results showed that the Indonesian textbook organises exponents into two distinct local definitions of function: repeated multiplication and exponential function. There are four different kinds of tasks based on the praxis block. The definition of an exponent, the characteristics of the exponent, the exponential function, and the graph of the exponential function. Even though there are not many differences between formal and textbook definitions of exponential and exponential functions, textbook tasks tend to be repetitive, so it is important to include assignments that encourage students to think more critically and creatively.Keywords: textbooks, praxeology, exponent, exponential function